Development and Use of Gene Therapy Orphan Drugs—Ethical Needs for a Broader Cooperation Between the Pharmaceutical Industry and Society - Kerpel-Fronius, Sandor; Baroutsou, Varvara; Becker, Sander; Carlesi, Roberto; Collia, Luis; Franke-Bray, Brigitte; Kleist, Peter; Kurihara, Chieko; Laranjeira, Luis Filipe; Matsuyama, Kotone; Naseem, Shehla; Schenk, Johanna; et al. (Frontiers in Medicine, 2020)
Gene therapy orphan medicinal products are frequently administered only once at an early age, in the hope to provide enough gene product to last for the entire life of the patients. The combination of an exceptionally large single payment and the life-long clinical follow-up needed represent new types of scientific and financial challenges for both the pharmaceutical industry and society. The authors propose the following ideas for optimizing the development of orphan gene therapy: (1) The parties should agree on a locally affordable drug price without calculating a very high premium price compensating for the low number of patients. In the case of high manufacturing costs, the companies should offer prolonged, 10 to 20 years long payment by installment with risk-sharing. (2) A close and long-lasting, contractually fixed cooperation should be established between the manufacturers and the health-care stakeholders of the local society for sharing the medical and scientific benefits as well as the risks and financial burdens of the clinical development. (3) To compensate for the decreased prices society should agree with the companies to finance the treatment and prolonged observation of a predetermined number of additional cases as well as to continue the long-term follow-up of the already treated patients as required by regulatory authorities. The organization and financial coverage of the long-term clinical cooperation program should be precisely defined. Our proposal adds medical and scientific values to the primarily commercially oriented drug pricing agreements.